Activation of ErbB-2 via a hierarchical interaction between ErbB-2 and type I insulin-like growth factor receptor in mammary tumor cells. - Balaña, Maria Eugenia (2001)
The present study focused on interactions between signaling pathways activated by progestins and by type I and II receptor tyrosine kinases (RTKs) in mammary tumors. An experimental model in which the synthetic progestin medroxyprogesterone acetate (MPA) induced mammary adenocarcinomas in Balb/c mice was used. MPA-stimulated proliferation, both in vivo and in vitro, of progestin-dependent tumors induced up-regulation of ErbB-2 protein levels and tyrosine phosphorylation of this receptor. Combinations of antisense oligodeoxynucleotides (ASODNs) directed to ErbB-2 mRNA with ASODNs directed to the insulin-like growth factor-I receptor (IGF-IR) were used to study the effect of the simultaneous block of these receptors on the MPA-induced proliferation of epithelial cells from the progestin-dependent C4HD line. Neither synergistic nor additive effects on the inhibition of MPA-induced proliferation of C4HD cells were observed as a result of the combination of these ASODNs. Suppression of IGF-IR expression by ASODNs resulted in complete abrogation of MPA-induced phosphorylation of ErbB-2 in C4HD cells, whereas blockage of ErbB-2 did not affect IGF-IR phosphorylation. These results show the existence of a hierarchical interaction between IGF-IR and ErbB-2, by means of which IGF-IR directs ErbB-2 phosphorylation. We demonstrated, for the first time, that this hierarchical interaction involves physical association of both receptors, resulting in the formation of a heteromeric complex. Furthermore, confocal laser microscopy experiments demonstrated that MPA was able to induce co-localization of ErbB-2 and IGF-IR. This hetero-oligomer was also found in MCF-7 human breast cancer cells in which association of IGF-IR and ErbB-2 was induced by heregulin and IGF-I.